Reducing Production Waste Using Lean Manufacture - Tommy Anandra Sunardi; Mokh Suef (Direktorat Riset dan Pengabdian Masyarakat (DRPM), ITS, 2019)
Currently, in globalization era, business competition in the fertilizer industry in Indonesia is very tight. This spurred the company to continue improving production results in terms of quality, quantity, price, and timeline of delivery to its customers. PT. JM Fertilizo (PT. JMF) is a company engaged in the processing of mining products that produce fertilizer for export purposes. One of the products delivered by PT. JMF is fosfat powder and Granule fertilizer. The company data shows in 2016 the company able to produce 550 tonnes / month and in 2017 able to produce 350 tonnes / month. Furthermore, there are still many products that can't meet customers requirement and several delays in product delivery. This problem causing inefficiency and decrease in production capacity. Therefore, this study was conducted to reduce the problems that exist in PT. JMF. The study which applied tools from Lean manufacturing, named value stream mapping and root cause analysis method has a conclusion that inappropriate process and waiting are the most dominant waste.